Estimating the population size of gay, bisexual, and other men who have sex with men in four major provinces in Canada: A descriptive study using data from a population-based survey - Felipe Tavares Duailibe; David Moore; Mark Hull; Viviane D. Lima (PLoS ONE, 2025)
Background Estimating the size of key populations is critical for effective research and policy development. We estimated the population size of gay, bisexual, and other men who have sex with men (GBM) based on different definitions and compared the demographic composition of the GBM and non-GBM populations in Canada. Methods This descriptive study used data from the 2015–2016 and 2019–2020 Canadian Community Health Survey (CCHS) cycles. We selected men aged 18–64 years who had valid responses to the sexual identity and sexual behaviour contents. We explored different combinations of the survey questions to estimate the size of the GBM population in Canada and conducted a separate analysis for Canada’s four most populous provinces, comparing sociodemographic characteristics. Results Using a definition of GBM combining sexual identity and behaviour (i.e., men who identify as gay or bisexual or who had sex with men in the last 12 months), the weighted proportion of GBM in the 2015–2016 cycle was 2.7% (95% Confidence Interval (CI) 1.9%–3.4%) in Alberta, 3.5% (95% CI 2.7%–4.4%) in British Columbia, 4.1% (95% CI 3.2%–4.9%) in Ontario, and 4.8% (95% CI 4.0%–5.7%) in Quebec. In the 2019–2020 cycle, the weighted proportion of GBM (i.e., men who identify as gay, bisexual or pansexual, or who had sex with men in the last 12 months) was 4.4% (95% CI 3.3%–5.4%) in British Columbia and 4.7% (95% CI 3.9%–5.4%) in Ontario. Overall, compared to non-GBM, GBM were more likely to be single/never married, have an annual household income of less than $30,000, live in medium and large population centres and have lower mean age. Conclusion Our estimates showed sexual orientation discordance in Canada. Our findings also suggested that the GBM population might be increasing over time.